The hidden epidemic of occult hepatitis B and C among injection drug users (IDUs): A call for action - Elkashef, Kholoud A.; Abdel Fattah, Nelly R.; Mesbah, Noha M.; El-shaarawy, Fatma F.; Amer, Mahmoud; Fakhr, Ahmed Elsadek; Gharib, Amal F.; Abo-Elmatty, Dina M.; Abdel-Hamed, Asmaa R. (International Journal of Health Sciences, 2025)
Objective: This study aims to determine the prevalence of Occult Hepatitis B and C Infections among Egyptian injection drug users (IDUs) and identify key risk factors contributing to their occurrence within this high-risk group. Methods: In this cross-sectional study, 200 Egyptian IDUs were assessed. Participants were negative for Hepatitis B surface antigen and hepatitis C virus (HCV) RNA, with anti-HCV positive patients who achieved sustained virologic response after treatment included. Quantitative polymerase chain reaction (PCR) was used to detect HCV RNA in plasma and peripheral blood mononuclear cells, while HBV DNA was identified via nested PCR. Comparisons were made between Occult Hepatitis B infection (OBI) positive and OBI negative subgroups, as well as between other comprehensive income (OCI) positive and OCI negative subgroups. A significance level of 0.05 was set, with P-values below this indicating statistical significance. Statistical comparisons between OBI and OCI-positive and negative groups were performed using the Mann–Whitney U test and Chi-square test. Results: OBI was found in 32% of IDUs, while OCI was detected in 42% of IDUs, and was present in 53.6% of seropositive individuals. All OBI patients showed a significant increase in all liver function tests, while OCI patients had significant elevations in alanine transaminase and aspartate transaminase values. HIV coinfection was identified in 39.1% and 26.1% of OBI and OCI cases respectively. OBI and OCI coinfection were detected in 31 patients. Conclusion: Hidden infections such as OBI and OCI remain an overlooked public health issue in Egypt’s IDU population. These findings highlight the need for targeted strategies to address these reservoirs of infection and could inform similar approaches in countries with comparable HBV/HCV epidemiology.